2006
DOI: 10.1073/pnas.0511037103
|View full text |Cite
|
Sign up to set email alerts
|

Quorum signal molecules as biosurfactants affecting swarming in Rhizobium etli

Abstract: Swarming motility is suggested to be a social phenomenon that enables groups of bacteria to coordinately and rapidly move atop solid surfaces. This multicellular behavior, during which the apparently organized bacterial populations are embedded in an extracellular slime layer, has previously been linked with biofilm formation and virulence. Many population density-controlled activities involve the activation of complex signaling pathways using small diffusible molecules, also known as autoinducers. In Gramnega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
99
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(109 citation statements)
references
References 42 publications
6
99
0
4
Order By: Relevance
“…To coordinate such cooperative ventures, bacteria have developed methods of cell-to-cell signaling (14)(15)(16)(17)(18)(19), including direct physical interactions by extra membrane polymers (20)(21), secretion of extracellular materials like lubricating surfactin (22)(23), biochemical communication such as quorum sensing and chemotaxis signaling (by using mediators ranging from simple molecules and polymers to peptides and complex proteins) (24)(25)(26)(27)(28)(29), and exchange of genetic information (by plasmids and viruses) (30)(31)(32). Bacterial communication-based cooperation can lead to colony morphogenesis, coordinated gene expression, regulated cell differentiation, and division of tasks.…”
mentioning
confidence: 99%
“…To coordinate such cooperative ventures, bacteria have developed methods of cell-to-cell signaling (14)(15)(16)(17)(18)(19), including direct physical interactions by extra membrane polymers (20)(21), secretion of extracellular materials like lubricating surfactin (22)(23), biochemical communication such as quorum sensing and chemotaxis signaling (by using mediators ranging from simple molecules and polymers to peptides and complex proteins) (24)(25)(26)(27)(28)(29), and exchange of genetic information (by plasmids and viruses) (30)(31)(32). Bacterial communication-based cooperation can lead to colony morphogenesis, coordinated gene expression, regulated cell differentiation, and division of tasks.…”
mentioning
confidence: 99%
“…Since surfactants and other surface wetting agents may facilitate surface translocation by reducing surface tension, we also investigated the presence of surfactants in the seed exudates using a water droplet spreading assay (Daniels et al 2006), in which a drop of water was placed on top of swarm plates supplemented with the exudates and droplet spreading was observed; surfactants were not detected in the exudates using this method (data not shown). …”
Section: Seed Exudates and Plant Extracts Influence Flagellin Gene (Fmentioning
confidence: 99%
“…Swarming in R. leguminosarum (Tambalo et al 2010c) and the closely related species Rhizobium etli (Daniels et al 2006) have recently been reported and partially characterized. In R. leguminosarum bv.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR amplifications were performed using primers SPI-1559 and SPI-1713 (Table 2). The resulting 460 bp fragments were digested with XbaI and EcoRI, cloned into pUC18, confirmed by sequencing and subcloned into pFAJ1708 (Daniels et al, 2006), resulting in pCMPG13402 (referred to as pFosA) and pCMPG13403 (referred to as pFosA R119A ), constitutively expressing fosA + and fosA R119A , respectively. Plasmids were introduced into P. aeruginosa PAO1 by electroporation (Choi et al, 2006) to obtain strains CMPG13411 and CMPG13435, referred to as PAO(pFosA) and PAO(pFosA R119A ), respectively.…”
mentioning
confidence: 99%